Experiencia mística y epistemología: un diálogo entre Ciencia y Misticismo - Cadavid Ramírez, Lina Marcela de la Milagrosa (2023)
The epistemological crisis suffered by science in the early twentieth century made it possible for scientific thought to establish a dialogue with disciplines and discourses that the positivist vision of science had previously considered pseudoscientific. Furthermore, this dialogue was encouraged by the same scientists who saw the potential for serious reflection on issues that seemed to have been ruled out for scientific thought. The following article falls within the framework of the possibility of this dialogue, specifically between science, epistemology and mysticism, for the review of the prospects that have developed around the understanding of mystical experience, from epistemology and science today.